Effects of Apelin on Cardiovascular Aging - Zhou, Ying; Wang, Yong; Qiao, Shubin; Yin, Liang (Frontiers in Physiology, 2017)
Apelin is the endogenous ligand of APJ, the orphan G protein-coupled receptor. The apelin–APJ signal transduction pathway is widely expressed in the cardiovascular system and is an important factor in cardiovascular homeostasis. This signal transduction pathway has long been related to diseases with high morbidity in the elderly, such as atherosclerosis, coronary atherosclerotic heart disease, hypertension, calcific aortic valve disease, heart failure and atrial fibrillation. In this review, we discuss the apelin–APJ signal transduction pathway related to age-associated cardiovascular diseases.